Digital Transformation in Hospitality Operations: Evaluating the Effectiveness of Smart Service Technologies in Urban Hotels - Ahmad Zainunnuri, Fakhri (Politeknik Siber Cerdika Internasional, 2025)
Digital transformation is reshaping hospitality operations, particularly in urban hotels where technological innovation is increasingly essential for maintaining service quality and competitiveness. This study evaluates the effectiveness of innovative service technologies—such as contactless systems, AI-driven personalization, automated service platforms, and IoT-enabled room features—in enhancing operational performance and guest experience. A quantitative research design was employed, using a structured questionnaire distributed to 200 guests who had recently stayed in urban hotels implementing innovative services. Data were analyzed using Structural Equation Modeling (SEM) to assess relationships among smart service attributes, technology acceptance, operational efficiency, and guest satisfaction. The results show that usability and reliability are the strongest-performing attributes, significantly influencing technology acceptance. Technology acceptance was found to mediate the relationships among smart service attributes, operational efficiency, and guest satisfaction, underscoring its pivotal role in digital adoption. Innovative services also demonstrated a substantial positive impact on service delivery speed, process accuracy, and workload reduction. Comparative analysis indicated significant differences in usability and satisfaction across age groups and stay frequency. Overall, the findings validate the conceptual framework and emphasize the importance of user-centered technological design, trust-building, and personalized digital experiences. This study contributes theoretical insights into innovative hospitality systems and provides practical guidance for hotels seeking to optimize digital transformation strategies in urban environments.